Survey on Emerging Security Mechanisms for Medical Cyber Physical Systems (International Journal of Engineering and Computer Science, 2017)
Medical Cyber Physical System (MCPS) is able to transmit and process the data collected from health monitoring systems, which consists of BAN. The acquired data is transmitted to private or public cloud which contains set of algorithms for analysing the patient data. These medical data should be kept secret. After analysing these data, the feedback is given to the doctors to take corrective action. This system includes data acquisition which is capable of acquiring data from body area networks, data aggregation which concentrate the gathered signal information, cloud processing which includes many analysis algorithms and action layer which produce either physical action or decision support. Each of its layer contain hardware such as sensors and cloud computing architectures etc. So, the data should be secured in each layers. So many normal encipher mechanisms are used. Also, emerging encryption technology such as homomorphic encryption standards used in MCPS.